1993
DOI: 10.1104/pp.101.4.1181
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrin Accumulation and Export by Isolated Barley (Hordeum vulgare) Plastids (Effect of Diphenyl Ether Herbicides)

Abstract: We have investigated the formation of porphyrin intermediates by isolated barley (Hordeum vulgare) plastids incubated for 40 min with the porphyrin precursor 5-aminolevulinate and in the presente and absence of a diphenylether herbicide that blocks protoporphyrinogen oxidase, the enzyme in chlorophyll and heme synthesis that oxidizes protoporphyrinogen I X to protoporphyrin IX.In the absence of herbicide, about 50% of the protoporphyrin I X formed was found in the extraplastidic medium, which was separated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
91
0
4

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(99 citation statements)
references
References 27 publications
4
91
0
4
Order By: Relevance
“…There is a good physiological argument that this may be the case : mitochondria cannot synthesize haem, although they do contain ferrochelatase, and therefore chloroplasts must supply either haem or haem precursors to mitochondria and the rest of the cell. The efflux of haem and other porphyrins from isolated chloroplasts has been observed [61][62][63] . Possibly there are two haem-synthesis pathways in the chloroplast : one for photosynthetic uses and the other for non-photosynthetic and\or extrachloroplastidic haem.…”
Section: Regulation Of Mg-chelatase and Ferrochelatase At The Branch-mentioning
confidence: 99%
“…There is a good physiological argument that this may be the case : mitochondria cannot synthesize haem, although they do contain ferrochelatase, and therefore chloroplasts must supply either haem or haem precursors to mitochondria and the rest of the cell. The efflux of haem and other porphyrins from isolated chloroplasts has been observed [61][62][63] . Possibly there are two haem-synthesis pathways in the chloroplast : one for photosynthetic uses and the other for non-photosynthetic and\or extrachloroplastidic haem.…”
Section: Regulation Of Mg-chelatase and Ferrochelatase At The Branch-mentioning
confidence: 99%
“…3) Peroxidizing herbicides, including oxyfluorfen and acifluorfen, are photodynamically active and competitively block the substrate-binding region of Protox. [4][5][6][7] The acute toxicity of oxyfluorfen is a result of the accumulation of Protogen IX, which is oxidized in the cytoplasm to Proto IX by a nonspecific plasma membrane-bound peroxidase. 8,9) Proto IX in the cytoplasm is not metabolized by the porphyrin biosynthetic pathway because Mg-chelatase and Fe-chelatase, which use Proto IX as a substrate, are located in chloroplasts and mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…These data supported the view that, when plastid Protox is inhibited, Protogen IX migrates from the plastid to be oxidized to Proto IX by a PMbound Protox-like activity. Jacobs and Jacobs (1993) recently demonstrated that Protogen IX is exported at high levels from intact etioplasts treated with a Protox-inhibiting diphenyl ether herbicide. The accumulated extraplastidic Proto IX apparently does not readily reenter the porphyrin pathway; Plant Physiol.…”
mentioning
confidence: 99%